B Cell-Derived Extracellular Vesicles Reveal Residual B Cell Activity in Kidney Graft Recipients Undergoing Pre-Transplant Desensitization - Cucchiari, David; Tubita, Valeria; Rovira, Jordi; Ramirez-Bajo, Maria J.; Banon-Maneus, Elisenda; Lazo-Rodriguez, Marta; Hierro-Garcia, Natalia; Borràs, Francesc E.; Ventura-Aguiar, Pedro; Piñeiro, Gastón J.; Martorell, Jaume; Peri, Lluís; et al. (Frontiers in Medicine, 2021)
Background: Living-donor kidney transplant (LDKT) recipients undergoing desensitization for Human Leukocyte Antigen (HLA)-incompatibility have a high risk of developing antibody-mediated rejection (ABMR). The purpose of the study is to evaluate if residual B cell activity after desensitization could be estimated by the presence of circulating B cell-derived extracellular vesicles (BEVs). Methods: BEVs were isolated by Sepharose-based size exclusion chromatography and defined as CD19+ and HLA-II+ extracellular vesicles. We analyzed stored serum samples from positive crossmatch LDKT recipients before and after desensitization at first post-transplant biopsy and at 12-month protocol biopsy (n = 11). Control groups were formed by hypersensitized patients who were not submitted to desensitization (n = 10) and by low-risk recipients (n = 9). A prospective validation cohort of 11 patients also included the analysis of B cells subpopulations in recipients' blood and lymph nodes recovered upon graft implantation, along with BEVs analysis before and after desensitization. Results: We found out that CD19+ and HLA-II+BEVs dropped significantly after desensitization and relapse in patients who later developed ABMR was evident. We validated these findings in a proof-of-concept prospective cohort of 6 patients who received the same desensitization protocol and also in a control group of 5 LDKT recipients. In these patients, B cell subpopulations were also studied in recipients' blood and lymph nodes that were recovered before the graft implantation. We confirmed the significant drop in BEVs after desensitization and that this paralleled the reduction in CD19+cells in lymph nodes, while in peripheral blood B cells, this change was almost undetectable. Conclusions: BEVs reflected B cell residual activity after desensitization and this could be a valid surrogate of humoral alloreactivity in this setting.